Ontologías políticas plurales en los procesos de transición sostenible - Cristina Zurbriggen; Laura Gioscia (L'Ordinaire des Amériques)
Despite scientific warnings about environmental issues, few advances have been identified to date oriented toward a sustainable transition. In this scenario, this paper aims to reflect on the relevance of addressing the political dimension and ontological conflicts in the study of transitions toward sustainability. Considering political ontologies allows for greater openness and understanding of diverse perspectives, recognizing that there are different realities and ways of seeing the world and that there is no single solution to all environmental problems. In doing so, it opens the possibility of moving towards multiple ontologies and promoting a sustainable transition that is more inclusive, fair, and adapted to our world's diversity of realities and perspectives. In order to contribute to these debates, this article proposes a critical reflection on the importance of considering political ontologies in addressing complex socio-environmental problems to move towards pluralistic governance. To this end, we examine political ontologies and the growing academic interest in incorporating the ontological dimension in environmental studies and the relevant contributions made by Latin America. Finally, we reflect on the relevance of valuing dissent in sustainable transitions and incorporating environmental pluralism in change processes.